Citational Politics and Justice: Introduction - Wyatt, Sally (KULA, 2026)
This introduction provides an overview of the thirteen articles which constitute this special issue about “citational politics and justice.” The issue begins with a discussion paper, followed by six research articles, one commentary, one project report, one teaching reflection, and finishes with three conversations. Authors reflect on the history and future of citation practices, and what they mean for the recognition of marginalised scholars, knowledges, and forms of output. The range of contributions offers insights into how more just scholarly practices can be promoted in teaching, research, publishing, and collaboration with academic and societal partners. Together, these articles provide ideas for achieving greater citational justice, and ultimately improving the quality of knowledge.